A study of the leather industry in the district of Cotacachi (Ecuador) according to the theoretical Marshallian-Becattinian scheme - Fernando Martín-Mayoral; Roberta Curiazi; Leonel Castro Ruales (Investigaciones Geográficas)
The present work is the first part of an ongoing investigation into the characteristic features of an Ecuadorian manufacturing district, using the Marshallian-Becattinian theoretical scheme as a reference framework. This article analyses the leather sector of Cotacachi (Province of Imbabura, Ecuador) to establish its contribution to the socioeconomic development of the territory, and determine if it can be considered an industrial district in Marshallian-Becattinian terms. Using quantitative and qualitative methods, an examination of its socioeconomic characteristics is offered with respect to the theoretical scheme of an Italian industrial district, based on the experience of Prato (Italy). The main conclusion is that the leather sector of Cotacachi is still in a state of embryonic development as an industrial district in the theoretical scheme of Marshall-Becattini. This is because there is no ‘industrial atmosphere’ that enables a ‘collective efficiency’ connected to innovative processes. The presence of micro-networks in its interior, which can potentially generate a ‘district effect’ as in the case of Prato, clashes with an almost complete absence of subcontracting initiatives, with no articulation between productive actors, nor relationships between companies (except for micro-networks), and a lack of adequate institutional support. The absence of these elements limits the development potential of the district.